Health Volunteers in Songhla AIDS Prevention and Control Project - Uahgowitchai, Charn (Journal of Health Science of Thailand, 1995)
STD and AIDS Center Region 12, with cooperation of World Vision of Thailand, had trained some health volunteers in the groups of commercial sex workers, fisherman communities and mobile fishermen. It was found that: 1. There was a good relationship between the government officials and the target groups. 2. The volunteers got the correct knowledge and attitudes in the prevention of STDs and HIV infection. 3. The target groups had received the correct knowledge and attitudes concerning prevention of STDs and HIV infections via the trained volunteers. To prevent and stop the spread of HIV infections, the use of health volunteers should be expanded. All private and government organizations must cooperate and help each other in simultaneously establishing more volunteers in all regions.